STRATEGI PENGEMBANGAN PEMBANGUNAN BERKELANJUTAN DAERAH PERBATASAN ANTAR NEGARA DI PROVINSI RIAU - Iqbal Miftakhul Mujtahid; Steven Anthony; Baskoro Wicaksono; Putri Hergianasari (Universitas Halu Oleo (UHO), 2023)
This article aims to anlyze the regional infrastructure development strategy in border areas between countries in Riau Province. This is Consistent with the geographical importance of the regency/city in Riau Province. The approach method used in this research is descriptive qualitative. How to collect data with documentation and indepth interviews. The results of this research explain that the infrastructure development strategy carried out for the coastal districts/cities in Riau Province includes; First, developing transportation links through sea transportation services in order to improve the quality and intensity of services in the maritime border area. Second, developing economic growth poles in border areas. It is based on regional idiosyncrasy, local capabilities and takes into account market opportunities aided by changes in infrastructure and data transfer, power, water and telecommunications. Infrastructure development must be carried out through planning that is synchronized with national development. So that the use of the Special Allocation Fund (DAK) for border areas can be realized properly, but the development that has been carried out so far is not in accordance with the national development proposed by the regional government